Compact Dual-Band, Wide-Angle, Polarization- Angle -Independent Rectifying Metasurface for Ambient Energy Harvesting and Wireless Power Transfer - Li, Long; Zhang, Xuanming; Song, Chaoyun; Zhang, Wenzhang; Jia, Tianyuan; Huang, Yi (IEEE transactions on microwave theory and techniques, 2021)
A dual-band and polarization-angle-independent rectifying metasurface (MS) with a miniaturized dimension and a wide incident angle range are presented in this article. The proposed structure consists of a single layer of periodic cell arrays with integrated diodes, a dc feed, and a load. A novel method of incorporating surface-mount components (e.g., diodes) into the texture is developed to simplify the structure. The matching network between MS and the nonlinear rectifier can be eliminated directly due to the multimode resonance and adjustable high-impedance characteristics of the MS. Moreover, the proposed MS can maintain high conversion efficiency by using different diodes without changing the overall topology. In addition, the proposed design can effectively capture incoming waves with arbitrary polarizations and a wide incident angle range of 60°. The 4× 4 MS array is fabricated and measured. Experimental results show that the proposed structure can achieve maximum efficiency of 58% at 2.4 GHz and 50% at 5.8 GHz with an input power of 0 dBm under different polarizations and incident angles. Importantly, it is also shown that the rectifying MS can maintain high efficiency over a wide power range from −3 to 10 dBm. The proposed design concept is very suitable for the adaptive wireless power supply of portable devices.